0305 The NIEHS GuLF STUDY: Questionnaire Results and Use of Job Exposure Matrices to Link Inhalation and Dermal Exposure Estimates to Study Subjects0305 The NIEHS GuLF STUDY: Questionnaire Results and Use of Job Exposure Matrices to Link Inhalation and Dermal Exposure Estimates to Study Subjects. (23rd June 2014) - Stewart, Patricia; Stenzel, Mark; Banerjee, Sudipto; Blair, Aaron; Cherrie, John; Engel, Lawrence; Groth, Caroline; Huynh, Tran; Kwok, Richard; McDowell, Wendy; Ng Gorman, Melanie; Ramachandran, Gurumurthy; et al.
Abstract : Objectives: To describe the activities of the GuLF STUDY participants responding to the Deepwater Horizon oil release in the Gulf of Mexico in 2010 and the process of developing job exposure matrices (JEMs) of exposure group/location/time period combinations to link inhalation and dermal exposures to the participants. Method: Information on activities performed by the participants in the NIEHS epidemiologic study were collected via questionnaire with details on almost 100 clean-up activities (e.g., skimming); dates; amount of time spent performing these activities; and the geographic location where these activities were performed. The questionnaire also collected information on frequency of exposure to various oil components onto various parts of the body and the use of protective equipment. JEMs of inhalation and dermal exposure estimates have been developed for total hydrocarbons for unique exposure group/vessel/time period combinations. Results: Preliminary data indicate over 6000 study subjects reported patrolling the beaches, reported removing tar balls, and reported removing oil or oily sand. Over 5000 collected oily plants, a similar number bagged oiled material and over 4000 decontaminated vessels or equipment of oil. Approximately one-third of the study subjects worked on the water; about 5% worked near the wellhead. Conclusions: Study subjects performed a variety of activities at multiple locations that resulted in different levels of inhalation and dermal estimates. These estimates will be used in the evaluation of exposure-response relationships in the epidemiologic study.